2009
DOI: 10.3109/15368370903206531
|View full text |Cite
|
Sign up to set email alerts
|

The Non Thermal Effect of Weak Intensity Millimeter Waves on Physicochemical Properties of Water and Water Solutions

Abstract: The comparative study of the effects of 5.8 mW/cm(2) Millimeter Waves (MMW) and near Infrared (IR) irradiation on thermal properties, specific adsorption rate (SAR), specific electrical conductivity (SEC) and hydrogen peroxide (H(2)O(2)) content of distilled water (DW), and physiological solutions (PS) was performed. The thermal effect of MMW irradiation appeared only after the first minute of irradiation, while the IR heating started from the first minute of irradiation. The heat fusion of frozen MMW-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…1Ea). This phenomenon was documented and more detail was studied in our previous study (Ayrapetyan et al, 2009). Temperature changes at distances from 5 -35 cm were found after 5 min MMW radiation ( Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…1Ea). This phenomenon was documented and more detail was studied in our previous study (Ayrapetyan et al, 2009). Temperature changes at distances from 5 -35 cm were found after 5 min MMW radiation ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…In previous (in vitro) experiments (Ayrapetyan et al, 2009), it was showed that influence both the direct NT effect of MMW and PS pretreated by NT effect MMW have the same modulating effect on heart muscle contractility of snails. On the basis of this data the cell bathing aqua medium was suggested as a target through which the NT biological effect of MMW is realized.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies carried out in our laboratory showed that EMF at frequencies less than 100 Hz has a depressing effect on water conductivity, which is accompanied by the increase in pH as a result of decreasing of CO 2 solubility (Stepanyan et al 1999;Akopyan and Ayrapetyan 2005). It was also shown that 4-Hz EMF and 4-Hz-modulated MMW treatment essentially changes the physicochemical properties of PS (Ayrapetyan et al 2009a), having modulating effect on snail neuron membrane's chemosensitivity (Ayrapetyan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature-dependent curve of PS H 2 O 2 contents has downward (in the range of 0 -48C) and upward (in the range of 4 -208C) characters (Ayrapetyan et al, 2009).…”
Section: Electromagnetic Biology and Medicinementioning
confidence: 97%